PERFORMANCE LECTURER ANALYSIS PERSPECTIVE COMPENSATION AND SELF-MOTIVATION - Firdaus Jauzi (Universitas Pamulang, 2022)
It is undeniable that the performance of lecturers is one of the main indicators in the implementation of quality higher education. The reason is that the performance of lecturers is directly related to teaching, research, and service. Interestingly, the performance of lecturers in the field of research has a great contribution to the development of science, so that it can be directly felt by students in educational activities and the community in service activities. This research wants to see how lecturer performance can increase positively and significantly based on compensation and self-motivation factors. The research method used is quantitative with multiple regression analysis. The object of research is a university in Central Sulawesi, with lecturers as the unit of analysis. Research data obtained through the distribution of questionnaires, with a simple random technique. The results showed that the increase in lecturer performance was positively proportional to the increase in self-motivation and compensation. This confirms that a lecturer will be more responsible for the achievement of Tri Dharma's performance if they get material support and have a positive personality.Keywords: Lecturer, Tri Dharma, Performance, Compensation, Self-Motivation